(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses ways to inform the public about the threat or occurrence of emergencies, as well as the organization of actions to inform the population and the leadership.Emergencies in the functioning of the state system. A comprehensive approach to solving the problems of public awareness and automation of information processes within the state system of emergencies was proposed..